Customer List Protection in Avoiding Unfair Business Competition Based on Law Number 30 of 2000 concerning Trade Secrets and Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition - David Ronaldo; Sudaryat Sudaryat (CV. Publikasi Indonesia, 2023)
Trade secrets are part of intellectual property, because the information contains economic value, however, the Trade Secret Act does not specifically state what can be classified as information with economic value, such as customer lists. Customer lists can be classified as information that can be protected by trade secret laws in Indonesia. Therefore, legal efforts are needed to protect this confidential information from acts of violation that can lead to unfair business competition